Kaanon ja marginaali Kulttuuriperinnön vaiennetut äänet - Hämäläinen, Niina; Tarkka, Lotte Maria (Kalevalaseuran vuosikirja, 2022)
Why the Kalevala and not the Kanteletar? The Kalevala Society's 101st Yearbook maps the processes of canonizing and marginalizing in traditions, cultural heritage and literature by focusing on the fringes of cultural ideals and norms. How and using which criteria have researchers, artists and materials of cultural production been lifted up or pushed aside? What kind of nations would have emerged if writing the nation had rested on the alternatives: the marginal rather than the canonical genres? A look into the blind spots and fringes of culture and research reveals the endless movement in and between hierarchically positioned spheres of culture. Listening to margins changes not only the canon but also the idea of canon.